2007
DOI: 10.1093/ageing/afm093
|View full text |Cite
|
Sign up to set email alerts
|

Sit-to-stand as home exercise for mobility-limited adults over 80 years of age GrandStand SystemTM may keep you standing?

Abstract: In a highly variable population of older adults with mobility limitations, low-intensity functional home exercise of repeated sit-to-stands using the GrandStand System improved Berg Balance Scale score while low-intensity progressive resistance training did not. While statistically significant, the improvement in Berg Balance Scale score was modest raising the issue of what extent of change in score is clinically significant in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 30 publications
2
80
1
1
Order By: Relevance
“…Repetitive STS exercises are used as an effective homebased exercise intervention strategy, particularly for the elderly (Slaughter et al 2015;Rosie and Taylor 2007). However, there is no information about the exercise intensity (METs) of repetitive STS exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive STS exercises are used as an effective homebased exercise intervention strategy, particularly for the elderly (Slaughter et al 2015;Rosie and Taylor 2007). However, there is no information about the exercise intensity (METs) of repetitive STS exercises.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of interest in assessing muscular strength, muscular endurance and functional performance was a little surprising on two counts. This being the importance of these measures for maintaining overall quality of life especially when using ADT 69 and as home-based exercise can significantly improve these outcomes in low-active older adults 75,79,80 . It is therefore recommended that future studies examine the potential for home-based exercise to improve prostate cancer patients' physical fitness and functional performance.…”
Section: Grade Recommendationsmentioning
confidence: 99%
“…However, it is typically not feasible to have large, expensive training equipment in day service centers that provide care for older adults. Previous research has shown that training with ankle-weight cuŠs and resistance bands, or using participants' body weight as resistance, to be eŠec-tive but no details were provided regarding the exercise intensity used in these interventions (Yamauchi et al, 2005;Rosie and Taylor, 2007;Shaw and Snow, 1998;Takeshima et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%